From JCPOA to MEWMDFZ: A possible resurrection for EU’s foreign policy? - Herrera, M. (2021)
Nuclear Weapons Free Zones (NWFZ) have remained a central nuclear disarmament proposal for different conflict regions such as the Middle East. For decades the Middle East has had a particular reliance on deterrence (Aly 1999; Rajmil 2015) which makes the implementation of any future NWFZ challenging. This approach towards regional security has been fostered by the ambiguity of Israel’s current nuclear deterrence dynamic, and more recently by the ongoing ambiguity of Iran’s nuclear policy. The political circumstances that characterize the Middle East therefore render a NWFZ or even a Weapons of Mass Destruction Free Zone (WMDFZ) unlikely in the foreseeable future. Big obstacles lie in the widespread perception that such a zone requires a level of cooperation which is beyond the capabilities of states in the region. This is compounded by the particular dynamics of Israel’s strategic relationship with its neighbors and its tendency to adopt independent security policies based on maximizing its military capabilities. Ongoing conflict is at the root of this mistrust: Israel’s occupation of Palestinian and other Arab territories, Iranian-Arab tensions, and Israeli-Iranian tensions all create an atmosphere of suspicion that has until now and with very few exceptions made productive arms control and disarmament negotiations impossible to convene.The development of a zone free of weapons of mass destruction in the Middle East has been indeed an eventful process. It is only in 2019 when formal talks at the UN level took place. However, these talks continued to not include key regional actors and focused on the framework of the Non-Proliferation Treaty review process rather than on regional politics. In this sense, the major international powers, and for the case of this paper, the EU, should seek mechanisms or procedures that take into account regional politics through which to regionalize existing nuclear non-proliferation frameworks. Based on this premise, this paper aims to discuss the potentialities present and created by the JCPOA as a regulatory and constraining framework for nuclear proliferation in the Persian Gulf region, and how a regionalization of its content could lead to a normative basis for implementing the MEWMDFZ